Academic Aleksandr Vasilievich Melnikov (1889–1958) (on the 130th anniversary of the birth) - A. A. Kurygin; S. D. Tarbaev; V. V. Semenov; I. S. Tarbaev (Вестник хирургии имени И.И. Грекова)
Academic Aleksandr Vasilievich Melnikov (Available at: URL: https://ru.wikipedia.org/wiki/Мельников,_Александр_Васильевич_(хирург))